PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR DAN KEAKTIFAN SISWA PADA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Liyana Sunanto; Dede Hadiansah; Muhamad Wahyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The author's concern about the low learning outcomes and student activity in science lessons in grade V of elementary school was the background to this research. The low factor of student learning outcomes is due to the low level of conceptual understanding and activeness of students, because many students do not understand the material they are studying. One effort that can be made is to apply the make a match learning model in science learning. This study aims to: 1) determine the effect of the make a match learning model on learning outcomes in social studies lessons for grade V at SDN V Gunungsari and 2) determine the effect of the make a match learning model on student activity in social studies lessons for grade V at SDN V Gunungsari. This study uses one group pretest-posttest design method. The instrument in this study uses test items to see learning outcomes and questionnaires to determine student activity in Science lessons. Data analysis for hypothesis testing uses paired sample t-test because the data is normally distributed. The results of the paired sample t-test for learning outcomes obtained a sig value (2-tailed) of 0.000 <0.05 and for the paired sample t-test value of the student activity questionnaire obtained a sig value (2-tailed) of 0.000 <0.05. Based on the results of this study, there is an influence of the make a match learning model on learning outcomes and student activity in the fifth grade of elementary school science lessons.